2018
DOI: 10.3390/cells7120248
|View full text |Cite
|
Sign up to set email alerts
|

ATG9A Is Overexpressed in Triple Negative Breast Cancer and Its In Vitro Extinction Leads to the Inhibition of Pro-Cancer Phenotypes

Abstract: Early detection and targeted treatments have led to a significant decrease in mortality linked to breast cancer (BC), however, important issues need to be addressed in the future. One of them will be to find new triple negative breast cancer (TNBC) therapeutic strategies, since none are currently efficiently targeting this subtype of BC. Since numerous studies have reported the possibility of targeting the autophagy pathway to treat or limit cancer progression, we analyzed the expression of six autophagy genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 36 publications
0
11
1
Order By: Relevance
“…In contrast to our study, decreased beclin-1 expression was observed in seventy percent of the breast tumors, and the protein levels were co-related to the mRNA levels [14]. However, Claude-Taupin, et al, [15] reported that no major difference in beclin-1 mRNA expression between tumor and healthy adjacent tissues. The current study revealed that TGF-β was significantly increased in breast carcinoma patients compared to control group (P value< 0.001) and this finding is affirmed by Ciftci, et al, [16] who have studied the expression level of TGF-β and established that the mean serum TGF-β level of breast cancer patients was considerably higher than controls.…”
Section: Correlation Between Beclin-1 and Tgf-β Expression Levelscontrasting
confidence: 99%
“…In contrast to our study, decreased beclin-1 expression was observed in seventy percent of the breast tumors, and the protein levels were co-related to the mRNA levels [14]. However, Claude-Taupin, et al, [15] reported that no major difference in beclin-1 mRNA expression between tumor and healthy adjacent tissues. The current study revealed that TGF-β was significantly increased in breast carcinoma patients compared to control group (P value< 0.001) and this finding is affirmed by Ciftci, et al, [16] who have studied the expression level of TGF-β and established that the mean serum TGF-β level of breast cancer patients was considerably higher than controls.…”
Section: Correlation Between Beclin-1 and Tgf-β Expression Levelscontrasting
confidence: 99%
“…ATG9B regulates cell autophagy process and if increased it can promote cell survival and proliferation of different types of neoplasms, such as renal cancer, breast cancer, cervical cancer, etc. [42][43][44]. Therefore, autophagy alteration could be an additional mechanism through which C-reactive protein can possibly promote endometrial cancer development and progression.…”
Section: Increased Crp As a Bad Prognostic Sign -Potential Mechanismmentioning
confidence: 99%
“…Several ARGs have been shown involved in pathogenesis of breast cancer. ATG9B has lower expression level in invasive breast tumors than matched normal tissues ( Claude-Taupin et al, 2018 ; Zhang et al, 2016 ). ATG9A inhibition led to an inhibition of in vitro cancer features ( Claude-Taupin et al, 2018 ).…”
Section: Discussionmentioning
confidence: 96%
“…ATG9B has lower expression level in invasive breast tumors than matched normal tissues ( Claude-Taupin et al, 2018 ; Zhang et al, 2016 ). ATG9A inhibition led to an inhibition of in vitro cancer features ( Claude-Taupin et al, 2018 ). GABARAPL1, as a tumor suppressor protein in breast cancer, is associated with a better outcome for patients with lymph node-positive breast cancer ( Berthier et al, 2010 ; Poillet-Perez et al, 2017 ).…”
Section: Discussionmentioning
confidence: 96%